1995
DOI: 10.1091/mbc.6.5.541
|View full text |Cite
|
Sign up to set email alerts
|

Polarized distribution of actin isoforms in gastric parietal cells.

Abstract: The actin genes encode several structurally similar, but perhaps functionally different, protein isoforms that mediate contractile function in muscle cells and determine the morphology and motility in nonmuscle cells. To reveal the isoform profile in the gastric monomeric actin pool, we purified actin from the cytosol of gastric epithelial cells by DNase I affinity chromatography followed by two-dimensional gel electrophoresis. Actin isoforms were identified by Western blotting with a monoclonal antibody again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 51 publications
6
87
2
Order By: Relevance
“…In the gastric parietal cell, there are at least two distinct pools of actin. At the cell cortex, γ-actin predominates whereas β-actin predominates in the canalicular region (Yao et al, 1995) The cortical actin pool is exquisitely sensitive to latrunculin B, which binds monomeric actin, whereas the formation of microvillar filaments appear to be highly resistant to this inhibitor as well as to cytochalasin D, which severs actin filaments (Ammar et al, 2001). Thus, at the cell cortex, a reduced affinity for actin could assist in the rapid remodeling of the actin cytoskeleton (Pollard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the gastric parietal cell, there are at least two distinct pools of actin. At the cell cortex, γ-actin predominates whereas β-actin predominates in the canalicular region (Yao et al, 1995) The cortical actin pool is exquisitely sensitive to latrunculin B, which binds monomeric actin, whereas the formation of microvillar filaments appear to be highly resistant to this inhibitor as well as to cytochalasin D, which severs actin filaments (Ammar et al, 2001). Thus, at the cell cortex, a reduced affinity for actin could assist in the rapid remodeling of the actin cytoskeleton (Pollard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al [15] revealed that most actin in the gastric gland is present in parietal cells, which are largely globular during the inactive resting secretion phase. However, during the active phase, actin forms a filamentous structure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, actin binds to intramembranous CD44 via phosphoryl ezrin in the plasma membrane [12][13][14]. It has previously been suggested that the above-mentioned morphological changes are induced and triggered by this cytoskeletal reorganization of β-actin [15][16][17].…”
Section: Introductionmentioning
confidence: 96%
“…Gastric glands were isolated from New Zealand White rabbits as modified by Yao et al (5). Briefly, the rabbit stomach was perfused under high pressure with PBS (2.25 mM K 2 HPO 4 , 6 mM Na 2 HPO 4 , 1.75 mM NaH 2 PO 4 , and 136 mM NaCl (pH7.4)) containing 1 mM CaCl 2 and 1 mM MgSO 4 .…”
Section: Isolation Of Gastric Glands and Aminopyrine Uptake Assay-mentioning
confidence: 99%
“…Within the gastric epithelium, ezrin has been localized exclusively to parietal cells and primarily to the apical canalicular membrane of these cells (3,4). Our previous studies have shown that gastric ezrin is co-distributed with the ␤-actin isoform in vivo (5) and preferentially bound to the ␤-actin isoform in vitro (6). It has been postulated that ezrin couples the activation of protein kinase A (PKA) to the apical membrane remodeling associated with parietal cell secretion (3,7).…”
mentioning
confidence: 99%